ANALYSIS OF EARNINGS MANAGEMENT BASED ON TOTAL ACCRUAL METHOD ON TOL, AIRPORT, PORTS SUB SECTOR COMPANY - Lenita Waty (Jurnal Ekonomis, 2019)
This study aimed to analyze the state of earnings and detect of earnings management actions conducted by companies on toll roads, airports, ports companies. Earnings management was measured using the total accrual formula. The data collected by using secondary data that has been published by Indonesia Stock Exchange. The data was processed by using the total accrual formula. Based on the result of the research, there were fluctuations in net profit during the period 2011 - 2015 on the toll road, airport, port companies with the average net profit of Rp. 1,719,139,658,710. The average value of total company accruals on the toll road, airport, port sub-sectors of 0.0065 meant that companies on the toll road, airport, port and other sub-sectors that take earnings management measured over the period 2011 - 2015 increase the company's profit.